Assessing environmental impact of wastes from animal husbandary practices in a tropical environment (2011)
Dumping of decaying wastes from animal pen as soil conditioners and pen wash water for irrigation is a common practice in developing countries. Releasing wastes to land and water may affect biological, chemical and physical properties of soils, plants and water. Hence, this paper assesses pollution effects of untreated animal husbandry wastes in tropical environment. Samplings were done on a daily basis over a 6-weeks period from the University of Ibadan Teaching and Research Farm which had been in operation for over 25-years. Assessing the degree of pollution was performed on the basis of Nitrate, Phosphorous, Potassium and Magnesium measurements in dump yard soil samples with average values ranging 0.38-0.40, 0.54-0.86, 0.16-0.37, and 0.58- 1.05 mg/I respectively. These values are higher than recommended FEPA standard, which makes the wastewater and slurries unsuitable for irrigated farming. Consumption of soluble nitrates and nitrites at this concentration could result to health problems such as methemoglobin. The pH of feacal discharge, wastewater, dump yard Soil being 6.5, 5.8, and 6.2 respectively were acidic. Heavy metals; Manganese and Iron ranged between 191-324 and 1.3-2.3 mg/kg respectively. Presence of heavy metals and trace elements in excess of FEPA/WHO recommended standards makes both feacal discharges and wastewater unsuitable for use as manure. Values of BODs, DO, and Temperature ranged 1350-1420mg/l, 0.55-0.75mg/l, and 27.0-0-33.5°C respectively. Observed high BODs and low DO values at an average temperature of 28-33°C fall short of the WHO water standard for irrigation, this is indicative of high polluting power of the wastewater.